Chrysomphalus aonidum as pest of citrus in Greece - Stathas, G.J.; Kozär, F. (ENTOMOLOGIA HELLENICA, 2006)
The presence of the scale insect Chrysomphalus aonidum (Linnaeus) (Hemiptera: Diaspididae), (the Florida red scale) is recorded in Greece and some data on its morphology are given. The coccid was found on the ornamental plant Dracaena sp. in Athens in the year 2000 and its rearing on potato tubes (Solanum tuberosum) and Cucurbita maxima is possible in the insectary. In January 2007 C. aonidum was found on heavily infested Citrus limon and Citrus sinensis, as well as on the less infested ornamental bushes Ficus benjamina and Ligustrum japonicum in outdoor conditions in the city of Kalamata (Peloponnese-southern Greece). In the past the presence of C. aonidum was recorded in Greece, but it was considered an occasional pest of citrus due to its difficulty to become acclimatized.